Pendidikan Karakter Dalam Kisah Nabi Musa a.s. - Indra Syahfari (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. The story of Prophet Moses is the longest and most complex story in the Holy Qur'an. This shows that within the story of Prophet Moses there is plenty of character education content. The contents of character education very important to be studied and may be an answer to this weakness of the nation's character.Aim. This study aims to find and understand the character education contained in the story of Prophet Moses in the Holy Qur'an.Methods. This research is descriptive qualitative research, in which the researcher analyzes, describes and summarizes the data related to the story of Prophet Moses.Results. The results of this study are the story of Prophet Moses as in the Holy Qur'an contains many characters education, namely: religious, honest, curiosity, hard work, social care, communicative friendly, love of knowledge, courteous, and responsible.